Challenges in cosmetic gynecology surgery: A case series (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Cosmetic and functional gynecology is a novel specialty that is rapidly gaining tractionacross the globe, particularly in Europe, Asia, and America. These intricate procedures enhance theesthetics and restore the physiological function of the genitalia. This relates very closely to womensexuality, dignity, self-esteem, and overall confidence. Self-esteem is often closely mirrored anddependent on a person’s perception of her genitalia, both functionally and more recently esthetically. Anincreasing number of gynecologists are gradually embracing this art of restoration as the demand rapidlyincreases among patients. The outcomes are sometimes not pleasing to the patients and may requirerevision.Case series: We present four case series of undesirable outcomes from labiaplasty andperineovaginoplasty. The surgical procedures had to be repeated in two instances because of spousaldemand or from the lady herself.Case 1: Reconstruction after Type IV female genital mutilation (FGM)A 46-year-old grand multipara with Type IV FGM presented with sexual dysfunction and psychosexualproblems arising from FGM. She requested reconstruction of the labia minora, restoration of the labiamajora, and perineovaginoplasty. Examination revealed partial clitoridectomy, a narrowed vaginalintroitus with the removal of the labia minora, and excision of the labia majora. The missing tissues madethe reconstruction technically difficult. Labia minora was reconstructed from the labia majora by thegrooving technique, and labia majora fat augmentation with perineoplasty was performed with goodoutcomes.Case 2: Perineoplasty revision.A 43-year-old, para 3+0, presented with complaints of lax vaginal muscles after her third delivery. All herdeliveries were normal, vertex. She sustained a second-degree perineal tear after her last delivery, whichwas repaired. She was started on Kegel’s exercises with no improvement. She had a perineoplasty donesuccessfully, but she healed with a small rent. A revision was performed with good results.Case 3: Perineoplasty revisionThe patient underwent vaginoperineoplasty, but the perineum healed with a little bump, which both thepatient and the spouse did not like. Revision of perineoplasty was performed with excellent outcomes.Case 4: Revision of an overly tight vagina after vaginoperineoplastyThe patient had previously undergone vaginoperineoplasty but felt it was not tight enough. However,three months after revision, the spouse complained of incomplete penetration, whereas the patientcomplained of pain at the fourchette. Another revision was performed to address their concerns withgood outcomes.Conclusion: Cosmetic gynecological procedures must achieve satisfactory outcomes and restore theclient’s genital esthetics and functionality. Although some procedures are technically challenging and mayrequire repeat procedures, patient satisfaction is key. Knowledge of pelvic anatomy and restorationtechniques is a prerequisite for achieving acceptable outcomes. Counseling of the couple is an integralpart of cosmetic gynecology to manage expectations and rule out psychosocial causes.